2020
DOI: 10.1038/s41598-020-70662-2
|View full text |Cite
|
Sign up to set email alerts
|

Quasicrystalline phase-change memory

Abstract: phase-change memory utilizing amorphous-to-crystalline phase-change processes for reset-to-set operation as a nonvolatile memory has been recently commercialized as a storage class memory. Unfortunately, designing new phase-change materials (PCMs) with low phase-change energy and sufficient thermal stability is difficult because phase-change energy and thermal stability decrease simultaneously as the amorphous phase destabilizes. This issue arising from the tradeoff relationship between stability and energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Many studies have examined the association between NO 2 and COVID‐19 66 , 10–74 . NO 2 , an endogenously generated oxidant, has a potential impact on COV19 epidemic transmission 75 .…”
Section: Epidemiological Study Between Air Pollutants and Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined the association between NO 2 and COVID‐19 66 , 10–74 . NO 2 , an endogenously generated oxidant, has a potential impact on COV19 epidemic transmission 75 .…”
Section: Epidemiological Study Between Air Pollutants and Covid‐19mentioning
confidence: 99%
“…16 A large body of clinical evidences suggested critical roles of a wide range of cytokines in the nosogenesis of COVID-19. 19 It has been confirmed that there is an uncontrolled "cytokine storm" in patients with poor prognosis, which is characterized by local and systemic pro-inflammatory factors, including interleukin (IL)−6, tumor necrosis factor-α (TNF-α) and IL-1β. [20][21][22][23][24] The adaptive immune system is mainly composed of B cells, CD4 + T cells (helper T cells) and CD8 + T cells (cytotoxic or killer cells), which react to pathogens in an antigen-specific way and produce protective immunity.…”
mentioning
confidence: 99%